'Who wants to go the outdoor rink?': a media analysis of Canada's outdoor rinks and the connection to Canada's national identity. Issue 4 (2nd October 2018) - Edwards, Jonathon; Kulczycki, Cory
ABSTRACT: Winter activities, such as outdoor skating are arguably part of Canada's identity; however, due to changing social, political, legal, economic, and environmental factors, one component of winter activities that is in jeopardy is the outdoor rink. The purpose of this study was to explore the media framing surrounding issues within media articles regarding outdoor rinks in Canada as it pertains to national identity and place meaning theory. This paper utilized the computer program – Leximancer – to facilitate a review of media frames contained within 65 newspaper and online news articles. Seven frames and five sub-frames depicting the public discussion about the state of outdoor rinks and their use in Canada were identified. Media frames were grouped into place meaning categories of: Place Characteristics, Socialization within a Place, and Activities that have Place Meaning. The meanings discussed here can inform policy and management wherein attempts are made to balance public and private access to outdoor rinks and the inherent issues faced by a hockey passionate culture.